Kontribusi Sikap Mandiri Dan Jenis Pekerjaan Orang TuaTerhadap Minat Berwirausaha Mahasiswa PendidikanAkuntansi Universitas Muhammadiyah SurakartaAngkatan 2013 - Kurniawati, Fitri; , Dr.Suyatmini,SE.,M.Si (2016)
The purposes of this research are: 1) determining the contribution independent attitude for the student interest in entreprenuership. 2) determining the contribution of parent occupation for the student interest in intreprenuership.3) determining the contribution independent attitude and parent occupation for the student interenst in entreprenuership. The subject of this research is the 2013 grade student of accounting who get entreprenuership lesson. Arround 180 students follow this lesson with 119 students as sample were taken by proportional random sampling for collecting the data, the researcher using that has been tested about the validity and reability. The data analiysis technique used is multiple linier regression analiysis. The result of the regression analiysis: Y= 10,368+0,307 (X1)+0,461 (X2), it's means that entreprenuership interest is influence by the independent attitude and the parent occupation based on the analiysis can be concluded that: (1) independent attitude significantly influence the interestet entreprenuership. It can be prove that the regression analiysis value show tcount > ttable : 4,139 > 1,980 with significance value 0,000 <0,05. (2) the occupation parent also has influence for the interest of interprenuership it can be prove that the regression analiysis value tcount > ttable : 6,650 > 1,980 with significance value 0,000 < 0,05. (3) the independent attitude and parent occupation have significant influence for the interest of entreprenuership. It can be prove that the regression analiysis value Fcount > F table : 34,857 > 3,072 with significant value 0,000 < 0,05. The variable independent attitude have big influence arround 14,7% the variable of parent occupation have influence 29,5%, it can be concluded thath both of independent attitude and parent occupation have significant value around 44,2% and 55,8% the other one is influence by the other variable who the writer forget